2021
DOI: 10.3390/ai2020016
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Together against the Pandemic: Learning Multiple Models on Tomography Images for COVID-19 Diagnosis

Abstract: COVID-19 has been a great challenge for humanity since the year 2020. The whole world has made a huge effort to find an effective vaccine in order to save those not yet infected. The alternative solution is early diagnosis, carried out through real-time polymerase chain reaction (RT-PCR) tests or thorax Computer Tomography (CT) scan images. Deep learning algorithms, specifically convolutional neural networks, represent a methodology for image analysis. They optimize the classification design task, which is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…To address the above issues, transfer learning was adopted to allow the DeepLabV3+ to be able to segment grapes with high accuracy on the condition that only a small dataset was provided. The basic idea of transfer learning is to transfer the knowledge gained in other fields to a new task [25]. In order to implement the transfer learning, the DeepLabV3+ was first trained on the PASCAL VOC2012, which contained tens of thousands of images with 20 classes.…”
Section: Transfer Learningmentioning
confidence: 99%
“…To address the above issues, transfer learning was adopted to allow the DeepLabV3+ to be able to segment grapes with high accuracy on the condition that only a small dataset was provided. The basic idea of transfer learning is to transfer the knowledge gained in other fields to a new task [25]. In order to implement the transfer learning, the DeepLabV3+ was first trained on the PASCAL VOC2012, which contained tens of thousands of images with 20 classes.…”
Section: Transfer Learningmentioning
confidence: 99%
“…The neural network ensemble is being used in various fields such as image classification and detection to improve performance and make a robust model [26][27][28][29]. Chen et al [26] classified a channel randomly selected for hyperspectral images and then ensembled each classifier with the majority voting to derive the final result.…”
Section: Rvm and Cnnmentioning
confidence: 99%
“…This model showed a state-of-the-art performance even using a 10× smaller dataset than previous studies. Manzo and Pellino [28] proposed a neural network ensemble model to diagnose COVID-19 disease from computer tomography images. They demonstrated that combining multiple models produces better results than using a single model.…”
Section: Rvm and Cnnmentioning
confidence: 99%
“…We used a standard thorax model from Ercleve [24] as a reference to determine thoracic abnormalities in COVID-19 sufferers. Several other research that use thorax imagery in identifying COVID-19 are the use of the internet of things (IoT) [25], adaptive stratification [26], social approachment [27], blood cell ratio [28], thoraxic surgery [29], tomography images [30], otolaryngology surgery [31], handheld optical system [32], SOM-LWL method [33], therapeutic effects [34], upper respiratory tract [35].…”
Section: Introductionmentioning
confidence: 99%